Thismia velaris and T. dasyantha, two new species of Thismia section Thismia subsect. Odoardoa (Thismiaceae) from Sarawak, Malaysia - Dančák, Martin; Hroneš, Michal; Sochor, Michal; Uvírová, Alena; Blažek, Vojtěch Tobias; Yunoh, Siti-Munirah Mat; Yiing, Ling Chea (Phytotaxa, 2025)
Thismia velaris and T. dasyantha (Thismiaceae), two new species from Sarawak (Malaysian Borneo), are described. Key distinguishing features, particularly in floral structure, are highlighted through comparative morphological analyses accompanied by illustrations. Additionally, phylogenetic relationships are assessed using molecular data, and both newly described species are placed within the broader evolutionary framework of Thismia. Both species, being characterized by vermiform roots and six free tepals of equal shape and size, are classified within Thismia sect. Thismia subsect. Odoardoa. Preliminary conservation assessments, following IUCN Red List criteria, suggest that both species may be at risk due to their restricted distributions and potential habitat threats. Through the discovery of T. velaris and T. dasyantha, the diversity and biogeographical patterns of Thismia in Borneo are further elucidated, emphasizing the need for continued exploration and conservation efforts.